Diseño de un modelo de administración de inventarios para empresas del sector fundición de acero, hierro gris y nodular para el sector automotríz (2017)
In gray and nodular iron steel foundries in Colombia, a standard is established in terms of consumption of raw materials essential for the manufacture of parts for the automotive industry and the metal-mechanical industry. For this reason, companies with the same characteristics as Fundicom S.A.S, Andes foundries, Sicolsa S.A.S, Bogotá metal and Fundiciones capital were grouped together to carry out this project.